2010
DOI: 10.1007/s10499-010-9321-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of VP28 DNA vaccine on white spot syndrome virus in Litopenaeus vannamei

Abstract: White spot syndrome virus (WSSV) occurs worldwide and causes high mortality and considerable economic damage to the shrimp farming industry. Considering the global environmental, the economic and sociological importance of shrimp farming, and the constraints of high intensity cultivation, development of novel control measures against the outbreak of WSSV become inevitable. In this study, we have explored the protective efficacy of DNA vaccination and tissue distribution of the recombinant plasmid in immunized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Similar attempts to vaccinate shrimps against WSSV using DNA vaccines have been carried out by Kumar et al (2008), Kono et al (2009), and Li et al (2010). Among these studies, Kumar et al (2008) showed a convincing survival of 66.6 % in shrimp injected with a plasmid expressing VP28 followed by WSSV challenge on 21 days postimmunization.…”
Section: Immunoprotection In Crustaceansmentioning
confidence: 80%
“…Similar attempts to vaccinate shrimps against WSSV using DNA vaccines have been carried out by Kumar et al (2008), Kono et al (2009), and Li et al (2010). Among these studies, Kumar et al (2008) showed a convincing survival of 66.6 % in shrimp injected with a plasmid expressing VP28 followed by WSSV challenge on 21 days postimmunization.…”
Section: Immunoprotection In Crustaceansmentioning
confidence: 80%
“…However, the intensity of DNA vaccine‐lpv28 expression declined and thus the protection of L. vannamei against WSSV infection, as the RPS value decreased significanlty after 14th day compared to that of 7th day (Li et al . 2010). VP28 transcripts obtained from expression vector was detected in haemocyte, hepatopancreas, muscle, stomach, gill, intestine, eyestalk, heart, epidermis, lymph organ, ventral nerve cord, testis and ovary at 1, 3 and 7 days post vaccination, while the survival rate of the vaccinated was 60% above the control group.…”
Section: Vp28 Encoded Dna Vaccinementioning
confidence: 99%
“…WSSV chứa 5 loại protein cấu trúc chính là VP28, VP26, VP24, VP19 và VP15; trong đó VP28 và VP26 là hai protein biểu hiện trên vỏ virus. Do tính kháng nguyên cao và khả năng kích thích hệ thống miễn dịch của tôm, VP26 và VP28 thường được sử dụng làm marker chẩn đoán virus hoặc kháng nguyên đích cho vaccine phòng WSSV (van Hulten et al, 2001;Witteveldt et al, 2004;Rout et al, 2007;Li X et al, 2010;Syed et al, 2011). rVP28 đã được nghiên cứu biểu hiện ở nhiều hệ thống khác nhau như E. coli, nấm men, baculovirus (Rajeev et al, 2005;Syedet al, 2009;Hou et al, 2011).…”
Section: Mở đầUunclassified